2020
DOI: 10.1007/s00134-020-06181-5
|View full text |Cite
|
Sign up to set email alerts
|

Neurally adjusted ventilatory assist in acute respiratory failure: a randomized controlled trial

Abstract: We hypothesized that neurally adjusted ventilatory assist (NAVA) compared to conventional lung-protective mechanical ventilation (MV) decreases duration of MV and mortality in patients with acute respiratory failure (ARF). Methods: We carried out a multicenter, randomized, controlled trial in patients with ARF from several etiologies. Intubated patients ventilated for ≤ 5 days expected to require MV for ≥ 72 h and able to breathe spontaneously were eligible for enrollment. Eligible patients were randomly assig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
51
0
3

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(55 citation statements)
references
References 33 publications
1
51
0
3
Order By: Relevance
“…It was also suggested that the mechanical ventilation of patients classified to these two clinical types of disease should also differ; those with stiff lungs should be ventilated in accordance with the recommendations for ARDS, and those with compliant lungs may be ventilated with higher tidal volumes (7–9 ml/kg ideal body weight) and lower PEEP (< 10 cmH 2 O) than recommended [ 49 ]. Subsequent studies conducted in larger patient populations did not confirm this observation [ 17 , 19 , 20 , 23 , 26 ]. Our review of the available literature, limited as it is to pooled data from multiple studies with different methodologies, also does not support the existence of a clinical dichotomy.…”
Section: Discussionmentioning
confidence: 95%
“…It was also suggested that the mechanical ventilation of patients classified to these two clinical types of disease should also differ; those with stiff lungs should be ventilated in accordance with the recommendations for ARDS, and those with compliant lungs may be ventilated with higher tidal volumes (7–9 ml/kg ideal body weight) and lower PEEP (< 10 cmH 2 O) than recommended [ 49 ]. Subsequent studies conducted in larger patient populations did not confirm this observation [ 17 , 19 , 20 , 23 , 26 ]. Our review of the available literature, limited as it is to pooled data from multiple studies with different methodologies, also does not support the existence of a clinical dichotomy.…”
Section: Discussionmentioning
confidence: 95%
“…We have reported [ 2 , 3 ] that severe hypoxemia with relatively well-preserved respiratory system compliance (Crs) measured under standard conditions is characteristic of COVID-19-ARDS, and it differs from ARDS of other causes (typical ARDS), while others did not recognize consistent differences [ 4 7 ]. However, the increased frequency of higher Crs in COVID-19-ARDS was noted by some of the same authors [ 4 , 5 ], and a significantly higher Crs associated with severe hypoxemia was recently documented [ 8 ]. The heterogeneous nature of ARDS allows that—at the population level—there may be wide overlap between COVID-19-ARDS and typical ARDS, and these observations continue to drive a debate [ 6 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…1. Of the 75 studies, 7 studies met all inclusion criteria and were included in the nal quantitative synthesis [29][30][31][32][33][34][35]. The seven included studies comprised a total of 683 patients.…”
Section: Results Of the Searchmentioning
confidence: 99%
“…One of them was a published conference abstract [29]. Of note, 5 of the 7 studies (4 RCTs, 1 crossover trial) were included in the metaanalysis of weaning success [29][30][31][32][33].…”
Section: Results Of the Searchmentioning
confidence: 99%